The Study of People's Acceptance Towards Online Banking - Nor Hasnida, Yob (2010)
The online banking was recognized in Malaysia in 2001 toward development of technology and allows people to manage their account and transactions using internet. However, this system not fully utilize regarding to the number of people visit the physical bank is still high. This also proved by the statistic of online banking subscribers using the online banking in Malaysia is not drastically increase as the statistic of internet user since 2006-2009. Theoretically, the increment for both statistics should be equal. Moreover, the criminal cases happen all over the world includes Malaysia and create the negative perception among people towards online banking. The others internal factors that could be considered is the motivation, understanding and awareness among the people to the online banking. All these reasons encourage the researcher to investigate what exactly the main factor attracts people to use online banking. However, the researcher is limiting the study by focus on the internal factors affect the number of people using the online banking, Malaysia. The study focused on intrinsic and extrinsic motivation represented by the perceived usefulness (PE), perceived ease of use (PEOU) and perceived enjoyment (PE) as the independent variables in this research. Whilst, the dependent variables signified by the people's acceptance to the online banking. The objectives of this study are examine the factors that influence people using the online banking based on demography, investigate the main factor that motivates people deal with online banking particularly in banking environment, examine the other factors which influence people choosing online banking and lastly to investigate the relationship between PU, PEOU and PE towards online banking. A survey was conducted by distributing questionnaires to a randomly selected sample of 150 people located within the Klang Valley, in Malaysia. However, only 120 questionnaires were returned and available to analyze. The location of the survey was selected in view of its advancement, development and implementation of IT applications as compared to other locations in Malaysia. By connecting to the internet only the user can apply the online banking. To achieve the research objectives, researcher used SPSS Version 16.0 to analyze the data from questionnaires. The value of Cronbach's alpha is 0.852 explained the reliability of the study. This study found that, the main factor attract people to use online banking is because of PU, where the analysis proved that PU is significant to the usage and PEOU. Logically, the people use the service because it very useful and they will patronize with it if it is ease to use. The results also revealed that most of working people patronize and familiar with online banking since most of them familiar with internet and have problem to visit the bank. Finally, the researcher hope that this study are valuable for future research, people and bank management in providing new insights about the online banking.